Daily Spiritual Experience and Religious Believe - R. Pasifikus Christa Wijaya (Journal of Health and Behavioral Science, 2019)
Spiritual experience is often realized as a personal reality that is different from the doctrine of religious beliefs, but whether spiritual experience and religious beliefs are two constructs that are not related to each other is still a subject of debate on this secular oriented world. This study aims to explain the relationship between daily spiritual experience and religious beliefs. The subjects in this study were 69 early adults. The method of data collection in this study was carried out using the Daily Spiritual Experience Scale-Short Form and Religious Belief and Values Scale-Short Form. The results of the research data were analyzed using the Pearson product-moment correlation technique. The result shows a positive relationship between daily spiritual experiences and religious beliefs. Religious beliefs and values can encourage someone to find feelings of love, peace, and happiness in their daily spiritual experiences.